2018
DOI: 10.1002/14651858.cd010315.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure targets for the treatment of people with hypertension and cardiovascular disease

Abstract: We found no di erences in total numbers of deaths, heart or vascular deaths, total heart problems, or vascular problems, nor in total serious harms, between lower and standard blood pressure goal approaches. Based on very little information, we found more dropouts resulting from drug-related harms in the lower blood pressure target group and no overall health benefit among people in the lower target group. Quality of the evidence The best available evidence does not support lower blood pressure goals over stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 92 publications
0
25
0
4
Order By: Relevance
“…A range of strategies including primary care management and reductions in sodium intake are known to be potentially effective in reducing the burden of this critical risk factor. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…A range of strategies including primary care management and reductions in sodium intake are known to be potentially effective in reducing the burden of this critical risk factor. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…People with hypertension and established cardiovascular diseases are at particular high risk in general population. [19,20] Therefore, the management of elevated BP is a critical component of the comprehensive clinical management of diabetes. Previous study had revealed that in well-controlled type 2 diabetic individuals moderate red wine drinking could raise awake BP and lower asleep BP.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Recent systemic reviews and metaanalyses have proposed that intensive BP-lowering treatment increases the risk of cardiovascular death without observable benefits; these studies have concluded that there is insufficient evidence to justify the lower BP goal. [24][25][26] A large retrospective cohort study in Hong Kong, which involved around 100 000 Chinese patients with diabetes mellitus receiving primary care services, identified that the SBP range for the lowest risk of cardiovascular diseases and allcause mortality was 130 to 134 mm Hg. In addition, a J-curve relationship between SBP and all outcomes of fatal and non-fatal cardiovascular diseases was observed, and patients with SBP <125 mm Hg were found to have significantly higher hazard ratio to all composite outcomes.…”
Section: Potential Harm Of a Lower Blood Pressure Definition And Treamentioning
confidence: 99%